Implementation of Five Action Ottawa Charter in Pos Kesehatan Kelurahan - Enggar Ayu Wardhani; Mohammad Zainal Fatah (LPPM STIKES KENDAL, 2020)
Five action of health promotions are an effective strategy to implement the good health promotion. The purpose of health promotion is to create health-contributed environment in order to stimulate human as the effort to change the behavior to be health oriented. Otawwa Charter has five actions to implement the good health promotion. The Pos Kesehatan Kelurahan is one of the program of desa siaga to facilitate health facility access for society become quite easier. The purpose of this research is to describe the implemented five actions of health promotion in Kelurahan Ngronggo Kediri. The importance of good health promotion strategy is the base of this research. This type of research is qualitative, the data conducted by indepth interview method using interview guide. The population of this research are 19 people contain with 17 health cadres and two medical staffs. The data of this research is primary and secondary data. Overall, kelurahan Ngronggo Kediri’s health station was good enough to implement five actions of health promotion even there was still one more aspect that was not fulfilled about to build a health public policy. four from five actions that were implemented could be a starting point to practice good health pro motion.